Peran Guru Dalam Membentuk Karakter Sosial Melalui Kemampuan Bersosialisasi Siswa di MI Nahdlatul Ulama Terpadu Sumbergempol Tulungagung - Nofeliu, Ima Yayang; Nikmati, Hamidah Abdul Shomad Elfin (SENTRI: Jurnal Riset Ilmiah, 2025)
This research is motivated by the decline in students' ability to socialize, interact, and establish healthy social relationships. Many students tend to be individualistic, lack empathy, and have difficulty in positive communication. The purpose of this study is to describe the role of teachers as educators, facilitators, and mentors in shaping social character through students' socialization skills at MI Nahdlatul Ulama Terpadu Sumbergempol Tulungagung. The approach used is a qualitative field research type with observation, interview, and documentation techniques. Data analysis was carried out through reduction, presentation, and drawing conclusions. The results show that the role of teachers as educators is realized through role models, moral value learning, and continuous development, as well as collaboration with families and the community. As facilitators, teachers provide facilities, support, and create a conducive learning environment through collaborative methods. As mentors, teachers direct and guide students according to their character and abilities through classical and individual guidance. Habits carried out by teachers are expected to shape social character through students' socialization skills.